Accuracy of ultrasonic fetal weight estimation: a comparison of three equations employed for estimating fetal weight - Tongsong T. (2014)
This study was conducted to compare the accuracy in estimating the fetal weight of three equations with ultrasound in 104 pregnant women. Equation I log 10 (EFW) = 1.85479 + 0.09008 (BPD) + 0.02466 (AC) Equation II log 10 (EFW) = 2.24784 + 0.09122 (FL) + 0.002798 (BPD x AC) -0.0010112 (AC x FL) Equation III log 10 (EFW) = -1.7492 + 0.166 (BPD) + 0.046 (AC) - 2.646 (AC x BPD)/1000 There was no difference in either the overall mean errors of 95 per cent CI among the three equations, except in the least error for equation II in these with birthweight of less than 2,000 grams and for equation III in these with birthweight of more than 3,000 grams. It was concluded, therefore, that predictions based on either equation I or II developed from local Thai population, which have an almost identical overall mean error when compared with one another or with Shepard's (i.e. equation III), can be used in our clinical.